Fungal community composition and diversity vary with soil depth and landscape position in a no-till wheat-based cropping system. Issue 7 (24th May 2018) - Schlatter, Daniel C; Kahl, Kendall; Carlson, Bryan; Huggins, David R; Paulitz, Timothy
ABSTRACT: Soil edaphic characteristics are major drivers of fungal communities, but there is a lack of information on how communities vary with soil depth and landscape position in no-till cropping systems. Eastern Washington is dominated by dryland wheat grown on a highly variable landscape with steep, rolling hills. High-throughput sequencing of fungal ITS1 amplicons was used to characterize fungal communities across soil depth profiles (0 to 100 cm from the soil surface) among distinct landscape positions and aspects across a no-till wheat field. Fungal communities were highly stratified with soil depth, where deeper depths harbored distinct fungal taxa and more variable, less diverse fungal communities. Fungal communities from deep soils harbored a greater portion of taxa inferred to have pathotrophic or symbiotrophic in addition to saprotrophic lifestyles. Co-occurrence networks of fungal taxa became smaller and denser as soil depth increased. In contrast, differences between fungal communities from north-facing and south-facing slopes were relatively minor, suggesting that plant host, tillage, and fertilizer may be stronger drivers of fungal communities than landscape position. Abstract : Fungal communities vary with soil depth in deep loess soils.